Live Donor Kidney Transplantation Outcomes Following Establishment of the First Kidney Transplant Center in Ethiopia. (August 2017) - Ahmed, Momina M.; Bekele, Mahteme; Abebe, Engida; Tadesse, Mekdim; Berhe, Tekleberhan; Worku, Berhanu; Redae, Berhane; Abebe, Zerihun; Tedla, Fasika; Abate, Mersema; Jayaram, Deepa; Pestana, Jose Medina; et al.
Abstract : Introduction: Kidney transplantation (TXP) is the preferred treatment for patients with end stage renal failure in industrialized countries, but its availability is very limited in Sub-Saharan Africa. In Ethiopia, this option was accessible for only those few who could afford to travel abroad with their living donors for donation and TXP. In collaboration with faculty from the University of Michigan (UM), the Federal Democratic Republic of Ethiopia, National Kidney Transplant Center, the first Ethiopian kidney transplant program, was launched at Saint Paul's Hospital Millennium Medical College (SPHMMC) in Addis Ababa in Sept 2015. This study reports on live donor (LD) and recipient (REC) TXP outcomes to date. Methods: Outcomes are presented for all LD and REC who participated in LD TXP at SPHMMC from Sept 2015 through March 2017. All procedures were performed by SPHMMC TXP surgery fellows in collaboration with UM faculty and the SPHMMC nephrologists. Results: A total of 36 patients underwent LD TXP. All but five LD were related to the REC, while the remaining were REC spouses. For the LD, there was a M: F ratio of 0.7:1, with a median age of 31.0 years. For the REC, there was a M: F ratio 6.2: 1 of, with a median age of 34.3years. The etiology of renal failure was unknown in 75% of REC. Most TXP was after initiation of hemodialysis. Average duration of hemodialysis was 12.5 months. 50% of REC had a history of blood transfusion. All kidneys were recovered by hand-assisted laparoscopic donor nephrectomy, except for one patient who required conversion to open nephrectomy because of extensive adhesions from tuberculosis. All REC received basiliximab induction. Tacrolimus, mycophenolate, and prednisolone were the most frequently used immunosuppressive combination. There was one hyperacute rejection, and one patient with a functioning graft died of infective endocarditis at day 27. Infection (20%), diarrhea (13%), nephrotoxicity (8%), and post-transplant diabetes mellitus (8%) were the most common REC complications. Conclusion: Despite challenges arising from a resource-limited setting, outcomes of LD TXP performed at SPHMMC are comparable to international standards. Prospects for sustainable LD TXP in Ethiopia are promising.